Technical Efficiency of Wet Season Melon Farming - Yekti, Ananti; Darwanto, Dwidjono Hadi; Jamhari, Jamhari; Hartono, Slamet (Universitas Negeri Semarang, 2017)
Melon is one of high-value horticulture commodity which is cultivated widely in Kulon Progo regency. The nature of agricultural products is heavily dependent on the season, so it causes the prices of agricultural products always fluctuated every time. In wet season the price of agricultural products tends to be more expensive. Melon cultivation in wet season provide an opportunity to earn higher profits than in the dry season. The price of agricultural products tends to be more expensive in wet season, thus melon cultivation in wet season prospectively generate high profits. In order to achieve high profitability, melon farming has to be done efficiently. Objective of this study was to 1) determined the factors that influence melon production in wet season 2) measured technical efficiency of melon farming and 3) identified the factors that influanced technical efficiency. Data collected during April â€“ June 2014. Location determined by multistage cluster sampling. 45 samples of farmers who cultivated melon during wet season obtained based on quota sampling technique. Technical efficiency was measured using Cobb-Douglas Stochastic Frontier. The result reveals that 1) land use, quantity of seed, K fertilizer contributed significantly increasing melon production, while N fertilizer decreased melon production significantly 2) technical efficiency indeces ranged from 0.40 to 0.99, with a mean ofÂ 0.77; 3) farmerâ€™s experience gave significant influence to technical efficiency of melon farming in wet season.